Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1159/000066242
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Assay of Five Enzymatic Activities in the Stratum Corneum Using Tape-Strippings

Abstract: The report describes a method for the assay of five enzymatic activities involved in establishing the stratum corneum permeability barrier: β-glucocerebrosidase, acid phosphatase, phospholipase A2 (PLA2) and two serine proteases: chymotrypsin and its activator in the stratum corneum, trypsin. The specific activities of these different enzymes have been determined along with their pH profiles and sensivities to specific inhibitors. It can be noted that only two presented a pH optimum simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 26 publications
3
64
1
Order By: Relevance
“…The acidic pH is also required for normal permeability barrier function 19,8 , and several other key SC functions. For example, the activity of acidic, lysosomal type, lipid processing enzymes is required to fully establish the permeability barrier 13,12,16,36 , and an acidic pH controls the activity of proteases necessary for SC integrity and desquamation 9,38,33,17 . We recently demonstrated that the Sodium-Hydrogen-Exchanger 1 (NHE1) plays a key role in establishing this critical acidic SC milieu 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The acidic pH is also required for normal permeability barrier function 19,8 , and several other key SC functions. For example, the activity of acidic, lysosomal type, lipid processing enzymes is required to fully establish the permeability barrier 13,12,16,36 , and an acidic pH controls the activity of proteases necessary for SC integrity and desquamation 9,38,33,17 . We recently demonstrated that the Sodium-Hydrogen-Exchanger 1 (NHE1) plays a key role in establishing this critical acidic SC milieu 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies [3][4] we described and analyzed the enzymes involved in generating this protective envelope and showed that in dry, non-eczematous atopic dermatitis, the phosphatase-like and trypsin-like activities are altered. The present study pursues these investigations in the same type of pathology but in cases involving an inflammatory component.…”
Section: Introductionmentioning
confidence: 99%
“…And the PTD group compared with the PSD group showed more irregular granular keratin in granular cells and immature keratin formation. It is well documented that ACP activity is increased in damaged tissues, [44][45][46] and ACP activity in PTD group was significantly higher than that of PSD group. Therefore, these results suggest that PPD skin toxicity in a tungstate supplemented diet is enhanced.…”
Section: Discussionmentioning
confidence: 84%